The effect of bone radiation on hematopoiesis: A literature review - Rendhy Tito Apreza; Soehartati A. Gondhowiardjo (Radioterapi & Onkologi Indonesia, 2021)
Over time, external radiation techniques have continued to evolve so that they can be used totreat bone malignancies for curative, postoperative adjunct, and metastases purposes. However,in the bone, there is the bone marrow that is sensitive to radiation. Even sublethal doses cancause bone marrow microenvironment deficits, including a decrease in hematopoietic cells.There is a complex relationship between radiotherapy (RT) and the hematopoietic system.Acute radiation injury usually manifests as cytopenia: anemia, neutropenia, andthrombocytopenia. Several potential mechanisms regarding the effects of radiotherapy on bonemarrow, including direct damage to the hematopoietic stem cells (HSC), lead to decreasednumber and function. This literature review will discuss hematopoiesis, the effect of boneradiation on hematopoiesis, and its mechanisms.